Bullish and Bearish Strategies Based on Technical Analisys: MACD, RSI, and SO JII30 2025 - Miftahul Huda; Mufti Afif; Ahmad Suminto; Amelia Putri Arizka Zaharani (Institut Agama Islam Negeri Ponorogo, 2025)
The purpose of this study is to enhance public literacy in the use of Islamic investment applications to prevent fraud and minimize losses in stock trading. Along with global technology advancement, trading activities have become more effective and efficient, requiring individuals to be financially literate in managing their assets. One productive financial management strategy is investment in the Islamic capital market, which allows funds to grow without violating Sharia principles such as gharar and maisir. This study employs a descriptive qualitative method by analyzing time series data over six months, from January to June 2025. The data were analyzed using three technical indicators: Moving Average Convergence Divergence (MACD), Relative Strength Index (RSI), and Stochastic Oscillator (SO), to determine bullish and bearish positions in stock trading. The findings indicate that using a single technical indicator is ineffective in providing accurate buy and sell signals. In contrast, combining all three indicators proves to be more effective in improving the accuracy of technical analysis and supporting investment decisions that comply with Sharia principles. This research is expected to serve as a reference for novice investors to understand the importance of financial literacy and the application of technical analysis in Islamic stock investments.